Estudo experimental da cinética de secagem do abacate (Persea americana Mill.) - Alves, Suerda Bezerra (2010)
Biofuels obtained from the avocado have become most promising because of the great potential of oil that can be extracted from the pulp of the fruit and the ethanol that can be obtained from the fruit stone. In order to be able to take out oil from the avocado pulp, one must dry up the fruit first. The purpose of the present work has been to study the drying process used for sliced avocado based on mathematical models so as to simulate mass transfer during this procedure. The equations applied to the mathematical models were numerically solved, and, by using the method of the least squares, it was possible to obtain the Effective Diffusivity and the Mass Transfer Convective Coefficient. The experimental conditions studied during the drying operation required that the velocity set at 3m/sec at temperatures of 50, 60 and 70º C were taken into account. A thorough knowledge of the mass transfer coefficients was of paramount importance for the drying process, as the Coefficient of Convective Mass Transfer is associated to the product s organic and geometric influences as well as to the thermodynamic properties of the air. On analyzing the results, it was observed that a rise in temperature favored the process of mass transfer, increasing these coefficients. It was also noted that the Fick model did not fit the experimental data well; whereas the Newton model showed better results, being capable of predicting the mass transfer on the product surface. The results were most significant because they made known the mass transfer during the convective drying of the avocado pulp.